A randomised, double-blind, placebo-controlled phase IIB clinical trial of repeated application of gene therapy in patients with cystic fibrosis - Alton, E; Boyd, A; Cheng, S; Cunningham, S; Davies, J; Gill, DR; Griesenbach, U; Higgins, T; Hyde, S; Innes, J; Murray, G; Porteous, D (2013)
The UK Cystic Fibrosis Gene Therapy Consortium has been working towards clinical gene therapy for patients with cystic fibrosis for several years. We have recently embarked on a large, multi-dose clinical trial of a nonviral, liposome-based formulation powered for the first time to detect clinical benefit. The article describes the details of the protocol.